2013
DOI: 10.1021/jo302766k
|View full text |Cite
|
Sign up to set email alerts
|

Electrofugalities of 1,3-Diarylallyl Cations

Abstract: Heterolysis rate constants k1 of differently substituted 1,3-diarylallyl halides and carboxylates have been determined in various solvents. The linear free energy relationship log k1 = s(f)(N(f) + E(f)) was found to predict the heterolysis rates (log k1) of 1,3-diarylallyl derivatives with a standard deviation of 0.26, corresponding to a factor of 1.82 in k1, and maximum deviation in k1 of a factor of 5. Some systematic deviations are evident, however. Thus, 1,3-diarylallyl carboxylates always react faster and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…for the reaction of thiophene 2 with the CH 3 O − ion in methanol is 11.6 times larger than calculated (k2 calc ) according to Equation . The deviations between calculated rate constants from the three parameters (Equation ) and experimental rate constants have been observed by many authors . Zenz and co‐workers investigated the reactivities of a series of trans ‐ β ‐nitrostyrenes with various acceptor‐substituted carbanions in dimethyl sulfoxide solution at 20°C and demonstrated that calculated rate constants according to the linear free energy relationship (Equation ) deviate by less than a factor of 6 from those measured.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…for the reaction of thiophene 2 with the CH 3 O − ion in methanol is 11.6 times larger than calculated (k2 calc ) according to Equation . The deviations between calculated rate constants from the three parameters (Equation ) and experimental rate constants have been observed by many authors . Zenz and co‐workers investigated the reactivities of a series of trans ‐ β ‐nitrostyrenes with various acceptor‐substituted carbanions in dimethyl sulfoxide solution at 20°C and demonstrated that calculated rate constants according to the linear free energy relationship (Equation ) deviate by less than a factor of 6 from those measured.…”
Section: Resultsmentioning
confidence: 98%
“…They can also be employed for determining the electrophilicity parameters E of the two different positions of our thiophenes 1 and 2. [49][50][51][52][53][54][55][56][57] From the intercepts of these lines with the ordinate axis, values of the electrophilicity parameters E of unsymmetrical thiophenes 1 and 2 have been evaluated. For the addition to the 4-position, E values of -11.57 and -14.36 for the thiophenes 1 and 2 have been determined, respectively.…”
Section: Electrophilicity Parameters E Of Thiophenes 1 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear free energy relationship given in Eq. (1) [1][2][3], in which the electrophile is characterized by a single parameter (E) and the nucleophile is characterized by two parameters (N, s), has been applied to Scheme 1 describe quantitatively the reaction rates of a large variety of electrophile-nucleophile combinations in which nucleophilic addition is rate limiting [3][4][5][6][7][8][9][10][11][12][13][14][15]. The electrophilicity scale thus established presently covers a reactivity range of 32 orders of magnitude, from E = −23.80 for substituted diethyl benzylidenemalonate 4 [16] to E = 8.02 for the 3,5-difluoro-substitued benzhydrilium ion 5 [17].…”
Section: Introductionmentioning
confidence: 99%
“…By selection of the right metals, the merging of enamine catalysis with Lewis acid‐catalyzed reactions would be possible 92. When we were investigating alcohols compatible in our organocatalytic alkylation, we immediately found out that 1,3 diphenyl allylic alcohol was not a reactive substrate, due to its high electrophilicity 93. So, it was not possible to generate the corresponding carbenium ion.…”
Section: An Unexpected Journey: Carbenium Ions For Organocatalytic Snmentioning
confidence: 99%